(Un)official anthems as a means of the national diplomatic/statecraft momentum - Udovič, Boštjan (International journal of Euro-Mediterranean studies, 2020)
The article deals with the importance of (un)official anthems for statecraft in Slovenia. An analysis of the emergence, development and structural incorporation into the affairs of the state and its diplomacy for the Slovenian national anthem Zdravljica, as well as two unofficial anthems, Hej, brigade (Ljubljana) and Vstajenje Primorske (the Primorska Region), reveals that a song can only become an important source or means of statecraft if it is accepted by social groups, and its "statecraftness" must develop following the bottom-up principle. Only this way can a song gain the social legitimacy needed for it to become an effective means of creating, shaping and developing the diplomatic/ statecraft momentum of a country internally and externally
Keywords: Državne himne; Državni simboli; Himne; Hymns; National emblems; National songs